The Politics of Rural Russia, 1905-1914 - Haimson, Leopold (Indiana University Press, 1979)
This volume treats an important and hitherto neglected topic in modern Russian history: The political evolution of the Russian countryside in the early twentieth century. Eight scholars examine the political and social conservatism of rural Russia from the formation of the Duma following the revolution of 1905 until the outbreak of World War I.